The Impacts of Motocross Event on the Social, Economic, and Environmental Conditions of the Alue Kambuk Village, Nagan Raya Community - Masni, Melly; Marlinda; Futhira, Farah; Pratiwi, Syadillah (Jurnal Riset dan Pengabdian Masyarakat, 2024)
A district championship grasstrack and motocross event known as "Kejurda" was held in the Alue Kambuk Village circuit on September 24-25, 2022. This competition was organized and run by the Indonesian Motor Association (IMI). The planning and execution of the event had a significant and widespread influence on the people living in Alue Kambuk Village. The purpose of this study, then, is to investigate how the Alue Kambuk Village motocross circuit event affected the community's social, economic, and environmental conditions and how those conditions were affected by the event. According to the findings of this research, the motocross circuit event held at Alue Kambuk Village has not only provided great social and economic consequences to the community, but it has also caused detrimental environmental repercussions to the area surrounding Alue Kambuk Village.